Traditional bullying and cyberbullying victimization independently predict changes in problematic internet gaming in a longitudinal sample - Neumayer, Franziska; Jantzer, Vanessa; Lerch, Stefan; Resch, Franz; Kaess, Michael (Journal of adolescent health, 2023)
Purpose - Bullying and problematic Internet gaming (PIG) are two concerning phenomena among adolescents. Research suggests an association between them; however, longitudinal studies are scarce. Therefore, this study examined whether traditional and cybervictimization are prospective risk factors for PIG and how gender, school type, and age influence these relationships. - Methods - Adolescents (grades 5-13; N = 4,390) answered two surveys one year apart which were linked by individual codes. They were classified as “victims” based on the Olweus Bullying Questionnaire-Revised. Changes in PIG (T2-T1) were computed based on nine items reflecting the diagnostic criteria for DSM-5 Internet Gaming Disorder. - Results - Traditional and cybervictimization independently predicted changes in PIG. The emergence of traditional victimization only, cybervictimization only, and particularly, both forms of victimization simultaneously, was associated with an increase in PIG. A decrease in PIG was only found if victimization terminated in both contexts. Further, an additive effect was found if traditional victimization newly extended to cyberspace. For boys and B-level students, the emergence of traditional victimization was associated with a larger increase in PIG than for girls and A-level students, when compared to the absence of traditional victimization. For boys, this also applied for cybervictimization. - Discussion - The emergence of bullying victimization in either an offline or online context appears to be a risk factor for PIG. Importantly, victimization must be stopped in both contexts for a decrease in PIG. Therefore, prevention programs need to focus on bullying offline as well as online to counter PIG. Efforts should especially focus on boys and B-level students.